Ekstarsi Ciri Citra Ultrasonografi Abdomen pada Regional 3, 6 dan 8 Menggunakan Metode Gray Level Co-Occurance Matrix (GLCM) - Maslebu, Giner; Laga, Matius Umbu; Setiawan, Andreas (Lambung Mangkurat University Press, 2020)
ltrasonography is the most popular modality used for clinical applications to detect abnormalities related to abdominal organs such as the liver, kidneys, uterus and other organs. In the context of organ recognition, image processing techniques are needed to improve image quality without eliminating important information contained in it. The purpose of this study was to identify prominent features of organs found in regional 3 (left liver lobe), 6 (left kidney and spleen) and 8 (bladder and prostate) from the abdomen using the gray level co-assurance matrix (GLCM) method. with features that are used, among others: contrast, correlation, energy and homogenity in the direction 0°, 45°, 90° and 135°. The results obtained show that each organ has a GLCM value that varies between one organ and another organ, namely regional Hypochondrium Dexta for left liver lobe organ, contrast 〖5.1473 x10〗^(-4)-〖1 x10〗^(-3), corrlation 0.9786-0.9890, energy 0.9073-0.9754 and homognity 0.9995 - 0.9997. Lumbaris Sinistra Regional for left ginjla organ, contrast 〖3.8526 x10〗^(-4)- 〖6.2959 x10〗^(-4), corrlation 0.9737 - 0.9862, energy 0.9737 - 0.9862 and homognity 0.9997-0.9998 while spleen, contrast 〖6.0350 x10〗^(-4) - 9.3762 x 〖10〗^(-4), corrlation 0.9640-0.9812, energy 0.9493-0.9816 and homognity 0.9995 - 0.9997. Regional Hipogastrum in bladder organs, contrast 4.0614〖 x10〗^(-4)- 9.9296 〖x10〗^(-4), corrlation 0.9770 - 0.9890, energy 0.9085 - 0.9884 and homognity 0.9995 - 0.9998 for prostate organs, contrast 3.0383 〖x10〗^(-4)-3.1532 〖x10〗^(-4), corrlation 0.9727 - 0.9738, energy 0.9877 - 0.9885 and homognity 0.9998. The range values represent the organs studied. The results of the research obtained indicate that the features of GLCM can be used to identify organs in regions 3, 6 and 8.